Building strategic agility through user-driven innovation: the case of the Finnish public service sector. (2nd January 2018) - Liang, Liting; Kuusisto, Arja; Kuusisto, Jari
ABSTRACT: This paper investigates how to build strategic agility through the lens of user-driven innovation. Drawing on survey data collected in the public service sector in Finland, our study suggests that the strategic rigidity of public service organisations, assessed according to their strategic sensitivity, resource fluidity and leadership unity, can hamper their effective adoption of the user-driven innovation approach to build strategic agility. We propose a 4C model of building strategic agility through user-driven innovation, addressing the need of taking actions in four areas: commitment, competences, communications and climate. Our research highlights that actions in the four dimensions, which are closely interlinked and reinforce each other, should involve actors at different levels both internally and externally.